Pregunta
upstudy study bank question image url

\( 1 \leftarrow \) For \( f(x)=\frac{x}{x-4} \) and \( g(x)=-\frac{9}{x} \), find the following composite functions and state the domain of each. \( \begin{array}{llll}\text { (a) } f \circ g & \text { (b) } g \circ f & \text { (c) } f \circ f & \text { (d) } g \circ g\end{array} \) (a) \( (f \circ g)(x)=\square \) (Simplify your answer. Use integers or fractions for any numbers in the expression.)

Ask by Sandoval Murphy. in the United States
Feb 20,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) \( (f \circ g)(x) = \frac{9}{9 + 4x} \) Domain: \( x \neq 0, x \neq -\frac{9}{4} \) (b) \( (g \circ f)(x) = -9 + \frac{36}{x} \) Domain: \( x \neq 4, x \neq 0 \) (c) \( (f \circ f)(x) = \frac{x}{-3x + 16} \) Domain: \( x \neq 4, x \neq \frac{16}{3} \) (d) \( (g \circ g)(x) = \frac{81}{x^2} \) Domain: \( x \neq 0 \)

Solución

To find the composite functions \( f \circ g \), \( g \circ f \), \( f \circ f \), and \( g \circ g \), we will follow these steps: 1. **Calculate each composite function.** 2. **Determine the domain of each composite function.** ### Given Functions: - \( f(x) = \frac{x}{x-4} \) - \( g(x) = -\frac{9}{x} \) ### (a) Find \( (f \circ g)(x) \) This means we need to substitute \( g(x) \) into \( f(x) \): \[ (f \circ g)(x) = f(g(x)) = f\left(-\frac{9}{x}\right) \] Now, substitute \( -\frac{9}{x} \) into \( f(x) \): \[ f\left(-\frac{9}{x}\right) = \frac{-\frac{9}{x}}{-\frac{9}{x} - 4} \] Now simplify the denominator: \[ -\frac{9}{x} - 4 = -\frac{9}{x} - \frac{4x}{x} = -\frac{9 + 4x}{x} \] Thus, we have: \[ f\left(-\frac{9}{x}\right) = \frac{-\frac{9}{x}}{-\frac{9 + 4x}{x}} = \frac{-9}{-(9 + 4x)} = \frac{9}{9 + 4x} \] So, \[ (f \circ g)(x) = \frac{9}{9 + 4x} \] ### Domain of \( (f \circ g)(x) \) The domain of \( g(x) \) is \( x \neq 0 \) (since \( g(x) = -\frac{9}{x} \) is undefined at \( x = 0 \)). Next, we need to ensure that the output of \( g(x) \) does not make \( f(x) \) undefined. \( f(x) \) is undefined when \( x - 4 = 0 \) or \( x = 4 \). Set \( g(x) = -\frac{9}{x} = 4 \): \[ -\frac{9}{x} = 4 \implies -9 = 4x \implies x = -\frac{9}{4} \] Thus, the domain of \( (f \circ g)(x) \) is: \[ x \neq 0 \quad \text{and} \quad x \neq -\frac{9}{4} \] ### Final Answer for (a): \[ (f \circ g)(x) = \frac{9}{9 + 4x} \] Domain: \( x \neq 0, x \neq -\frac{9}{4} \) Now, let's proceed to calculate the other composite functions. ### (b) Find \( (g \circ f)(x) \) This means we need to substitute \( f(x) \) into \( g(x) \): \[ (g \circ f)(x) = g(f(x)) = g\left(\frac{x}{x-4}\right) \] Substituting into \( g(x) \): \[ g\left(\frac{x}{x-4}\right) = -\frac{9}{\frac{x}{x-4}} = -\frac{9(x-4)}{x} = -\frac{9x - 36}{x} = -9 + \frac{36}{x} \] ### Domain of \( (g \circ f)(x) \) The domain of \( f(x) \) is \( x \neq 4 \). Next, we need to ensure that the output of \( f(x) \) does not make \( g(x) \) undefined. \( g(x) \) is undefined when \( x = 0 \). Set \( f(x) = \frac{x}{x-4} = 0 \): \[ \frac{x}{x-4} = 0 \implies x = 0 \] Thus, the domain of \( (g \circ f)(x) \) is: \[ x \neq 4 \quad \text{and} \quad x \neq 0 \] ### Final Answer for (b): \[ (g \circ f)(x) = -9 + \frac{36}{x} \] Domain: \( x \neq 4, x \neq 0 \) ### (c) Find \( (f \circ f)(x) \) This means we need to substitute \( f(x) \) into itself: \[ (f \circ f)(x) = f(f(x)) = f\left(\frac{x}{x-4}\right) \] Substituting into \( f(x) \): \[ f\left(\frac{x}{x-4}\right) = \frac{\frac{x}{x-4}}{\frac{x}{x-4} - 4} \] Now simplify the denominator: \[ \frac{x}{x-4} - 4 = \frac{x - 4(x-4)}{x-4} = \frac{x - 4x + 16}{x-4} = \frac{-3x + 16}{x-4} \] Thus, we have: \[ f\left(\frac{x}{x-4}\right) = \frac{\frac{x}{x-4}}{\frac{-3x + 16}{x-4}} = \frac{x}{-3x + 16} \] ### Domain of \( (f \circ f)(x) \) The domain of \( f(x) \) is \( x \neq 4 \). Next, we need to ensure that the output of \( f(x) \) does not make \( f(x) \) undefined again. Set \( f(x) = \frac{x}{x-4} = 4 \): \[ \frac{x}{x-4} = 4 \implies x = 4(x-4) \implies x = 4x - 16 \implies 3x = 16 \implies x = \frac{16}{3} \] Thus, the domain of \( (f \circ f)(x) \) is: \[ x \neq 4 \quad \text{and} \quad x \neq \frac{16}{3} \] ### Final Answer for (c): \[ (f \circ f)(x) = \frac{x}{-3x + 16} \] Domain: \( x \neq 4, x \neq \frac{16}{3} \) ### (d) Find \( (g \circ g)(x) \) This means we need to substitute \( g(x) \)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To find the composite functions \( f \circ g \) and the others, we first start with their definitions and the functions provided: 1. **Calculating \( f \circ g \)**: \[ (f \circ g)(x) = f(g(x)) = f\left(-\frac{9}{x}\right) \] Now substituting \( g(x) \) into \( f(x) \): \[ f\left(-\frac{9}{x}\right) = \frac{-\frac{9}{x}}{-\frac{9}{x} - 4} = \frac{-\frac{9}{x}}{-\frac{9 + 4x}{x}} = \frac{-9}{-9 - 4x} = \frac{9}{9 + 4x} \] Therefore, \[ (f \circ g)(x) = \frac{9}{9 + 4x} \] 2. **Finding the domain of \( f \circ g \)**: - The function \( g(x) \) is defined for all \( x \neq 0 \). - The function \( f(x) \) is defined as long as \( x \neq 4 \). - Here \( g(x) = -\frac{9}{x} \) must not equal 4, i.e., \( g(x) \neq 4 \). - Thus, solving \( -\frac{9}{x} = 4 \) gives \( x = -\frac{9}{4} \). So the domain for \( f \circ g \) is \( x \in \mathbb{R}, x \neq 0, x \neq -\frac{9}{4} \). --- 3. **Calculating \( g \circ f \)**: \[ (g \circ f)(x) = g(f(x)) = g\left(\frac{x}{x-4}\right) \] Now substituting \( f(x) \) into \( g(x) \): \[ g\left(\frac{x}{x-4}\right) = -\frac{9}{\frac{x}{x-4}} = -\frac{9(x-4)}{x} = -\frac{9x - 36}{x} = -9 + \frac{36}{x} \] Therefore, \[ (g \circ f)(x) = -9 + \frac{36}{x} \] 4. **Finding the domain of \( g \circ f \)**: - The function \( f(x) \) is defined for \( x \neq 4 \). - The function \( g(x) \) is defined as long as \( g(x) \neq 0 \). In this case, \( g(f(x)) \) is defined when \( \frac{x}{x-4} \neq 0 \), which holds for all \( x \neq 0 \). - The restrictions are that \( x \neq 4 \) and \( x \neq 0 \). So the domain for \( g \circ f \) is \( x \in \mathbb{R}, x \neq 0, x \neq 4 \). --- 5. **Calculating \( f \circ f \)**: \[ (f \circ f)(x) = f(f(x)) = f\left(\frac{x}{x-4}\right) \] Now substituting into \( f(x) \): \[ f\left(\frac{x}{x-4}\right) = \frac{\frac{x}{x-4}}{\frac{x}{x-4} - 4} = \frac{\frac{x}{x-4}}{\frac{x - 4(x-4)}{x-4}} = \frac{\frac{x}{x-4}}{\frac{-3x + 16}{x-4}} = \frac{x}{-3x + 16} \] Therefore, \[ (f \circ f)(x) = \frac{x}{-3x + 16} \] 6. **Finding the domain of \( f \circ f \)**: - The initial restriction is \( x \neq 4 \). - We also check for when \( f(f(x)) \) is undefined (denominator equals zero): \( -3x + 16 \neq 0 \) implies \( x \neq \frac{16}{3} \). Thus, the domain for \( f \circ f \) is \(

preguntas relacionadas

Latest Pre Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad